INFLUENCE OF ROOTSTOCKS ON SENSITIVITY OF FLOWER BUDS TO FROST AND GENERATIVE PROPERTIES OF SWEET CHERRY CV. 'CARMEN’ : SENSITIVITY OF FLOWER BUDS TO FROST AND GENERATIVE PROPERTIES CV 'CARMEN’ - Djordjević, Boban; Djurović, Dejan; Zec, Gordan; Boškov, Djordje (Journal of Agricultural Sciences (Belgrade), 2021)
The study examined the influence of five vegetative rootstocks on the sensitivity of flower buds to frost during the period of ecological dormancy and production properties of sweet cherry cultivar Carmen. The study was carried out at a commercial orchard located at the experimental estate 'Radmilovac’ of the Faculty of Agriculture in Belgrade, in the five growing years (2020). Cultivar ‘Carmen’ was grafted on the following rootstock: ‘Colt’, ‘Gisela 5’, ‘Gisela 6’, ‘MaxMa 14’ and ‘Oblačinska cherry’. Winter frosts occurred during the ecological dormancy on March 14th and 15th. The intensity of frost was –7 °C. The percentage of damage and non-damage flowers per fruiting branches was determined by counting (50 flower buds per tree were taken from every part of the canopy and fruiting branches). The highest damage of flowers buds had trees grafted on Oblačinska cherry, average 77.2% of flower buds, while the lowest had trees grafted on ‘MaxMa 14’, average 24.3% of total flower buds. The significantly higher sensitivity of flower buds had short fruiting branch compared to long fruiting branch. The highest productivity had trees grafted on ‘Gisela 6’ and ‘MaxMa 14’.The study examined the influence of five vegetative rootstocks on the sensitivity of flower buds to frost during the period of ecological dormancy and production properties of sweet cherry cultivar Carmen. The study was carried out at a commercial orchard located at the experimental estate 'Radmilovac’ of the Faculty of Agriculture in Belgrade, in the five growing years (2020). Cultivar ‘Carmen’ was grafted on the following rootstock: ‘Colt’, ‘Gisela 5’, ‘Gisela 6’, ‘MaxMa 14’ and ‘Oblačinska cherry’. Winter frosts occurred during the ecological dormancy on March 14th and 15th. The intensity of frost was –7 °C. The percentage of damage and non-damage flowers per fruiting branches was determined by counting (50 flower buds per tree were taken from every part of the canopy and fruiting branches). The highest damage of flowers buds had trees grafted on Oblačinska cherry, average 77.2% of flower buds, while the lowest had trees grafted on ‘MaxMa 14’, average 24.3% of total flower buds. The significantly higher sensitivity of flower buds had short fruiting branch compared to long fruiting branch. The highest productivity had trees grafted on ‘Gisela 6’ and ‘MaxMa 14’.
Keywords: ecological dormancy, flower bud, percentage of damage, yield, fruit quality